Pengaruh Media Komik Digital berbasis Karakter terhadap Hasil Belajar Pendidikan Pancasila pada Materi Nilai-Nilai Pancasila Sila Pertama Siswa Sekolah Dasar - Moch Sabdan Adji Syahputra; Apri Irianto (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study aimed to examine the effect of character-based digital comic media on students' learning outcomes in Pancasila Education, particularly on the topic of the values of the first principle of Pancasila, among fifth-grade students at SDN Buncitan. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 50 fifth-grade students, divided into an experimental group (n = 25) and a control group (n = 25). Data were collected using a validated multiple-choice learning achievement test. Data analysis was conducted using the Shapiro–Wilk normality test, Levene's test for homogeneity, and the paired-samples t-test at a significance level of 5%. The results indicated that the mean score of the experimental group increased from 71.40 in the pretest to 86.60 in the posttest, while the control group increased from 67.20 to 71.20. The paired-samples t-test showed a significance value of 0.000 (p < .05), indicating a statistically significant improvement in learning outcomes in both groups after the learning process. However, the experimental group demonstrated a greater improvement than the control group. These findings suggest that character-based digital comic media has the potential to support the improvement of elementary school students' learning outcomes in Pancasila Education.